1999
DOI: 10.1377/hlthaff.18.5.193
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Declining Mental Health Service Use On Employees Of A Large Corporation

Abstract: This study examines concurrent changes in use of mental and general health services and in annual sick days among 20,814 employees of a large corporation. From 1993 to 1995 mental health service use and costs declined by more than one-third, more than three times as much as the decline in non-mental health service use. However, employees who used mental health services showed a 37 percent increase in use of non-mental health services and significantly increased sick days, whereas other employees showed no such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 11 publications
1
30
1
2
Order By: Relevance
“…There is a rough parallel between this finding and recent data reported by Rosenheck, Druss, Stolar, et al (1999), which showed that when one large corporation reduced its mental health benefits, the fraction of employees using outpatient mental health services per year declined by 11.3 percent over a two-year period and the fraction using inpatient mental health services increased by 18.2 per cent. (Note, however, that this shift in use patterns was not statistically significant.…”
Section: Overview Of Resultssupporting
confidence: 68%
“…There is a rough parallel between this finding and recent data reported by Rosenheck, Druss, Stolar, et al (1999), which showed that when one large corporation reduced its mental health benefits, the fraction of employees using outpatient mental health services per year declined by 11.3 percent over a two-year period and the fraction using inpatient mental health services increased by 18.2 per cent. (Note, however, that this shift in use patterns was not statistically significant.…”
Section: Overview Of Resultssupporting
confidence: 68%
“…Employers who have access to integrated databases on medical expenditures, pharmacy expenditures, workplace injuries, and disability can go part way to resolve this problem, as such databases can be used to evaluate the effects of changes in health plan benefits over time on a number of important employer costs. 15 However, even completely integrated databases typically lack two critical types of information that are needed to make a strong business case for expanded investment in employee health care. First, few companies have accurate individual-level job performance data for most of their employees.…”
mentioning
confidence: 99%
“…89,90 There also is evidence of an inverse relation between the costs associated with disability and service use. 91 The trade-off is that higher direct costs (mental health service use) will be associated with lower indirect costs or fewer losses (disability). That is, increased use of mental health services can decrease functional impairment.…”
Section: Health Services Costsmentioning
confidence: 99%